Microbiomes and Specific Symbionts of Social Spiders: Compositional Patterns in Host Species, Populations, and Nests - Busck, Mette Marie; Settepani, Virginia; Bechsgaard, Jesper; Lund, Marie Braad; Bilde, Trine; Schramm, Andreas (Frontiers in Microbiology, 2020)
Social spiders have remarkably low species-wide genetic diversities, potentially increasing the relative importance of microbial symbionts for host fitness. Here we explore the bacterial microbiomes of three species of social Stegodyphus (S. dumicola, S. mimosarum and S. sarasinorum), within and between populations, using16S rRNA gene amplicon sequencing. The microbiomes of the three spider species were distinct but shared similarities in membership and structure. This included low overall diversity (Shannon index 0.5-1.7), strong dominance of single symbionts in individual spiders (McNaughton’s dominance index 0.68-0.93), and a core microbiome (>50% prevalence) consisting of five to seven specific symbionts. The most abundant and prevalent symbionts were classified as Chlamydiales, Borrelia, and Mycoplasma, all representing novel, presumably Stegodyphus-specific lineages. Borrelia- and Mycoplasma-like symbionts were localized by fluorescence in situ hybridization in the spider midgut. The microbiomes of individual spiders were highly similar within nests but often very different between nests from the same population, with only the microbiome of S. sarasinorum consistently reflecting host population structure. The weak population pattern in microbiome composition renders microbiome-facilitated local adaptation unlikely. However, the retention of specific symbionts across populations and species may indicate a recurrent acquisition from environmental vectors or an essential symbiotic contribution to spider phenotype.